2005
DOI: 10.1677/joe.1.06161
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and hypothalamic distribution of the chicken thyrotropin-releasing hormone precursor cDNA

Abstract: In this paper we report the cloning of the chicken preprothyrotropin-releasing hormone (TRH) cDNA and the study of its hypothalamic distribution. Chicken preproTRH contains five exact copies of the TRH progenitor sequence (Glu-His-Pro-Gly) of which only four are flanked by pairs of basic amino acids. In addition, the amino acid sequence contains three sequences that resemble the TRH progenitor sequence but seem to have lost their TRH-coding function during vertebrate evolution. The amino acid sequence homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…For the mouse sequence, comparison of the genome-derived mRNA with the cDNA-derived mRNA sequence (13) showed many differences in the 5¢ UTR and several in the coding sequence and 3¢ UTR; an examination of sequences derived from the EST database showed complete agreement between these and the genome-derived sequence. For both chicken and medaka, the coding sequence derived from the genome-derived sequence was identical to that reported previously (15,17). Thus, the sequences derived here from genomic data generally agree well with previously published data and, where discrepancies occur, EST sequences support the genome-derived sequences.…”
Section: Synteny Analysissupporting
confidence: 87%
“…For the mouse sequence, comparison of the genome-derived mRNA with the cDNA-derived mRNA sequence (13) showed many differences in the 5¢ UTR and several in the coding sequence and 3¢ UTR; an examination of sequences derived from the EST database showed complete agreement between these and the genome-derived sequence. For both chicken and medaka, the coding sequence derived from the genome-derived sequence was identical to that reported previously (15,17). Thus, the sequences derived here from genomic data generally agree well with previously published data and, where discrepancies occur, EST sequences support the genome-derived sequences.…”
Section: Synteny Analysissupporting
confidence: 87%
“…Although TRH is evolutionarily conserved, its precursor sequence and the number of TRH progenitor copies show variation among different vertebrates (Iziga et al, ). Namely, the chicken TRH precursor contains four copies of the TRH progenitor sequence (Vandenborne, Roelens, Darras, Kühn, & Van der Geyten, ), rat and human have five and six copies, respectively (Lechan, Wu, Jackson, Wolf, et al, ; Yamada et al, ), Xenopus has seven copies, and six to eight copies were reported in fish (Aoki et al, ; Aoki, Masuda, Iigo, & Yanagisawa, ; Ohide, Ando, Yanagisawa, & Urano, ). In our in silico translation analysis of the pro‐TRH transcript of C. batrachus , we identified six copies of the TRH progenitor sequence in a prohormone spanning 255 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the chicken TRH precursor contains four copies of the TRH progenitor sequence (Vandenborne, Roelens, Darras, Kühn, & Van der Geyten, 2005), rat and human have five and six copies, respectively (Lechan, Wu, Jackson, Wolf, et al, 1986;Yamada et al, 1990),…”
Section: The Pro-trh Mrna Of C Batrachus and Its Comparison With Omentioning
confidence: 99%
“…S9). Interestingly, it contains only one canonical progenitor sequence (Glu-His-Pro-Gly) (in comparison to about five in mammals and birds, Vandenborne et al 2005 and references therein), but also 21 sequences with the His replaced with a Ser (Glu-Ser-Pro-Gly). The flanking sequence (Lys-Arg) is conserved.…”
Section: Genes Involved In Th Synthesis Regulationmentioning
confidence: 99%